Penerapan Model Pembelajaran Problem Based Learning (PBL) dan Kecerdasan Emosional Pada Materi Laju Reaksi Di SMA Negeri 1 Tompaso - Lempas, Vanesa Yunita (General Chemistry Journal, 2024)
This research aims to determine student learning outcomes after implementing the PBL learning model and emotional intelligence at SMA Negeri 1 Tompaso. This type of research is quantitative with a quasi-experimental approach. The research population was all class Xl students of SMA Negeri 1 Tompaso, totalling 167 people. The research sample was determined using a random sampling technique of 60 people. The instrunents used in this sheets and emotional intelligence questionnaires. Data analysisnormality tests, homogeneity tests, and hypothesis tests, namely t tests, f tests, and n-gain. The results of the research prove that the application pf the PBL learning model is quite effective in improving student learning outcomes as evidenced by the t-test, the mean pre-test value is 56.03 and pos-test 87.40 it can be seen that the post-test value is greater than the pre-test wit a significance of 0.000, meaning that H0 is accepted and H1 is rejected. Students’ emotional intelligence improves student learning outcomes, the results of the f test with SPSS show an fcount value of 8.184 with a significance 0.008<0.05, so emotional intelligence improves student learning outcomes